Disinfection of water inoculated with Enterococcus faecalis using solar/Fe(III)EDDS-H2O2 or S2O82− process. (1st July 2017) - Bianco, A.; Polo−López, M.I.; Fernández−Ibáñez, P.; Brigante, M.; Mailhot, G.
Abstract: In this study, the activation of H2 O2 and persulfate ions induced by solar photolysis of Fe(III)EDDS complex were investigated in water disinfection, applying solar AOPs processes. The use of Fe(III)EDDS complex maintains iron in soluble form until slightly basic pH and so the photolysis is efficient in a large range of pH compatible with natural waters. Moreover, for the first time, the impact of photogenerated hydroxyl and sulfate radicals on the inactivation of Enterococcus faecalis in water was studied. E. faecalis was proposed as alternative model microorganism given its higher resistance than the commonly used E. coli . The reactivity of hydroxyl radicals seems to be more efficient for the inactivation of such strain than the reactivity of sulfate radicals. Moreover, experimental results show that the concentration of Fe(III)EDDS complex is a key parameter for the inactivation of microrganisms. For the direct application in natural waters, the efficiency of the process in the presence of ubiquitous inorganic compounds, such as carbonate (HCO3 − /CO3 2− ) and chloride ions (Cl − ), was also investigated. Carbonates showed a strong reduction on the E. faecalis inactivation in all cases; meanwhile chloride ions enhanced the inactivation in the presence of persulfate as also shown by using a complementary kinetic modeling approach. A dual role of Fe(III)EDDS complex was established and discussed; essential for the generation of radical species but a trap for the reactivity of these same radicals. Highlights: A disinfection treatment based on advanced oxidation process (AOP) is proposed. Hydroxyl or sulfate radicals are generated with sunlight, Fe(III)-EDDS complex and hydrogen peroxide or persulfate. The disinfection efficiency is strictly correlated to the concentration of Fe(III)-EDDS and precursors. Impact of ubiquitous anions (carbonates and chlorides) on disinfection efficiency was investigated. The iron (III) complex has a dual effect on disinfection trends.